Nacionalismo judío y retórica antiedomita en la antigüedad - Tebes, Juan Manuel (El Colegio de México, 2011)
In 586 BC the city of Jerusalem was taken by Nebuchadnezzar’s army, and the ensuing sacking, destruction and burning are still remembered as the epitome of any major national catastrophe. Biblical scholars, following the relevant passages of the Hebrew Bible, have traditionally placed the burden of guilt for the devastation of Jerusalem on the Babylonians. However, there are some biblical passages that may allude to an involvement of the Edomites in these events. A close re-reading of these scarce sources demonstrates that the texts reproaching the Edomite behavior in 586 BC are not contemporary to the events they pretend to describe, they lack important factual details, and are full of theatrical imagery, a product of their negative attitude towards Edom. The author suggests that the belief of the Edomite involvement in the fall of Jerusalem and the destruction of the temple of Yahweh represents an ancient case of the “stab-in-the-back” tradition, so typical of modern defeated societies.